Dead center Clinton-Gore leadership and the perils of moderation - Burns, James MacGregor 1918-2014; Sorenson, Georgia J. (Scribner, 1999)
The authors examine "the leadership style of Bill Clinton and [offer] a forceful challenge to the strategy of centrism."--Jacket.
Keywords: Clinton, Bill <1946->; Gore, Albert <1948->; Clinton, Bill -- 1946-; Gore, Albert -- 1948-; USA -- Government; Geschichte 1883-1999; Politieke leiding; Politik; Moderation -- Political aspects -- United States; Political leadership -- United States; USA; United States -- Politics and government -- 1993-2001